Стилевые признаки общественно-политических практик населения Украины и факторы их формирования - Резник, А. (Социология: теория, методы, маркетинг, 2007)
The article presents empirical findings concerning style features of social and political practices among the population of Ukraine, as well as factors of their functioning. Due to factor analysis we have managed to obtain style features of political participation,which, in their turn have allowed designating four forms of political activity among the population of Ukraine, such as: "active contacting", "moderate ostentation", "active in conformism", and "radical ostentation". An inclination to take part in the forms of political activity requiring adequate resources or skills may be observed in the Ukrainian society nowadays. Besides, it is clarified that social and political practices of the population of Ukraine depend equally on socio-economic status and personal views and convictions.